2001
DOI: 10.1007/s003300101026
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric lipoma: report of a case with emphasis on US findings

Abstract: Mesenteric lipoma (ML) is a relatively rare disease that has been very infrequently reported. We present the clinical data and medical imaging results of an asymptomatic case with ML incidentally detected by sonography (US). On US the lesion was imaged as a well-demarcated hypoechoic mass with multiple linear echoes. The mass also changed location under probe compression. The lesion was imaged as a clearly demarcated non-enhanced homogeneous fat-density mass on CT. Color Doppler US and angiography confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 8 publications
0
27
0
3
Order By: Relevance
“…3) [12]. These findings are non-specific and may also be seen in various other conditions with mesenteric involvement, such as mesenteric lipomatous tumors [13]. CT is therefore always recommended to analyze any US-found mesenteric abnormalities.…”
Section: Us Featuresmentioning
confidence: 97%
“…3) [12]. These findings are non-specific and may also be seen in various other conditions with mesenteric involvement, such as mesenteric lipomatous tumors [13]. CT is therefore always recommended to analyze any US-found mesenteric abnormalities.…”
Section: Us Featuresmentioning
confidence: 97%
“…Thin fibrous septa may be present within the lesion, and the color Doppler examination shows no intra or perilesional vascularization. Another typical characteristic of lipomas is their mobility when pressure is exerted on the abdomen with the US transducer [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have reported cases of deep lipomas located in the thorax, mediastinum, chest wall and retroperitoneum. Cases of intraperitoneal lipoma are extremely rare (12,14,15).…”
Section: Fat-containing Tumors In the Pelvic Cavitymentioning
confidence: 99%